Avant la vida : aux origines de la légende de Jaufre Rudel, grand amour ou petite mort ? Les témoignages de Rofian et de Pétrarque - Roy Rosenstein (Revue des Langues Romanes)
According to legend, Jaufre Rudel died happy in the arms of the Countess of Tripoli. But an earlier or contemporary testimony states that the troubadour died on the high seas : Rofian maintains qe moric al passage, that he died during the crossing. Petrarch follows Rofian. He places Jaufre among the unhappy troubadours for he had set out to die and did not live to see his distant lady. Unlike Rofian and Petrarch, it was the author of the vida who had the brilliant idea to keep the dying poet alive long enough to reach Tripoli. The vida has him arrive in the Holy Land as good as dead: per mort. For him to expire in the arms of his distant love, whom he would have seen up close at last, was an inspired step, but only one step. Despite critics from Gaston Paris to Don Monson, simply the memory of Lanquan li jorn and an awareness of the troubadour’s noble ancestry leave too much room to the vida author’s imagination. Rofian provides the missing link in showing the troubadour died on his way. The role of the imagination in the vida – necessary and worthy – is limited to keeping the poet alive long enough to reach the Countess’s arms.